STRATEGI KREATIF ORANG TUA SINGLE PARENT DALAM MEMBANGUN SIKAP EMPATI ANAK SELAMA MASA PANDEMI COVID-19 - Sari Puteri Larastati; Erni Munastiwi (POTENSIA: Jurnal Kependidikan Islam, 2021)
This study aims to determine how the creative strategies of parents who are single parent status in building empathy attitude of children during the COVID-19 pandemic. This research uses a qualitative research method of phenomenology type. The results showed that the form of a single parent's creative strategy in building a child's empathy attitude during the pandemic began with training to care for plants, animals, and helping parents at home. Whereas practicing tolerance can begin by teaching children to appreciate differences, then to practice tolerance, done by respecting the efforts and abilities of their children. Respect his child when learning to fasting even though it is not full day. This situation will make the children do things with a sense of security and comfort without having to consider the demands from parents.